Direct chemical vapor deposition synthesis of large area single-layer brominated graphene - Hasan, Maria; Meiou, Wang; Yulian, Liu; Ullah, Sami; Ta, Huy Q; Zhao, Liang; Mendes, Rafael G; Malik, Zahida P; Ahmad, Nasir M; Liu, Zhongfan; Rümmeli, Mark H (RSC advances, 2019)
Graphene and its derivatives such as functionalized graphene are considered to hold significant promise in numerous applications. Within that context, halogen functionalization is exciting for radical and nucleophilic substitution reactions as well as for the grafting of organic moieties. Historically, the successful covalent doping of sp2 carbon with halogens, such as bromine, was demonstrated with carbon nanotubes. However, the direct synthesis of brominated graphene has thus far remained elusive. In this study we show how large area brominated graphene with C-Br bonds can be achieved directly (i.e. a single step) using hydrogen rich low pressure chemical vapor deposition. The direct synthesis of brominated graphene could lead to practical developments.